Penerapan manajemen risiko pada startup digital: Antara ketahanan dan inovasi - Audyzza, Keysa Fahradine (Maliki Interdisciplinary Journal, 2025)
The growth of digital startups presents complex risk challenges, ranging from market uncertainty to technological dynamics. This article discusses the importance of implementing adaptive and integrated risk management within the digital startup ecosystem. Risk management is not merely a mitigation tool; when managed strategically, it can serve as an enabler of innovation and competitive advantage. An approach based on ISO 31000, combined with Lean Startup principles, and supported by a collaborative and transparent organizational culture, has proven to enhance organizational resilience. This study emphasizes that balancing resilience and innovation is key to successful risk management in digital startups. The analysis shows that startups that systematically implement a risk management framework are able to adapt more quickly to changes in the business environment and reduce potential losses due to uncertainty. Furthermore, the integration of risk management and innovation strategies encourages a more data-driven, flexible, and responsive decision-making process to market needs. Thus, the implementation of risk management not only strengthens business stability but also serves as a foundation for sustainable growth. This article is expected to provide conceptual and practical contributions for digital startups in developing a dynamic, innovative risk governance model that meets the demands of the digital transformation era.